In Vitro Evaluation of the Accuracy of Intraoral Scanners for Anterior and Posterior Dental Restorations - Reihane Rafienezad; Mitra Iesaie; Kamran Kargar; Sayed Shojaedin Shayegh (Mashhad University of Medical Sciences, 2022)
Introduction: Passing through the traditional methods of impression making and using the latest technology of digital scanners forces us to compare the positive and negative characteristics of these tools with those of the usual methods adopted in dentistry. One of the most important concerns regarding digital formatting is the accuracy of these scanners. This laboratory study was conducted to evaluate the effect of the topography of the prepared tooth and the location of the tooth in the maxillary arch on the accuracy of the intraoral scanners, taking into account the parameters of precision and trueness.Materials and Methods: In this study, two canine and molar mandibular teeth were used, which were prepared for all-ceramic restoration. The use of ceramic die in this study provided us with the advantage of eliminating the need to use powder. Each ceramic sample was scanned 10 times by CEREC Omnicam and 3Shape Trios 3 scanners. The reference scanner was Open Tech. Finally, using the software, the STL format of the scans was prepared, and the obtained data were compared with the study reference scanner to assess precision and trueness. Statistical analysis of data was performed to find the differences using the Shapiro-Wilk test and paired t-test. Results: The results of the present study showed that in the molar teeth, the highest value and mean of the precision and trueness parameters were observed in the 3Shape Trios 3 scanner. However, the CEREC Omnicam scanner showed the lowest value and mean ​​of precision and trueness. No significant difference was observed between the two types of scanners in canine teeth in terms of mean precision and trueness.Conclusion: It can be claimed that in preparing the molar tooth for an all-ceramic restoration by intraoral scanners in the molar tooth, the 3Shape Trios 3 scanner was more accurate than the CEREC Omnicam. Nevertheless, there was no such significant difference in canine teeth.